Amorphous nickel sulfide / nickel nanosheet electrocatalyst as well as preparation method and application thereof
By loading an amorphous nickel sulfide/nickel nanosheet film on the foam nickel surface, the problems of insufficient performance and complex preparation of nickel sulfide electrocatalysts in the prior art are solved, and efficient, stable and low-cost HER electrocatalysts are achieved, and the preparation method is simple.
Patent Information
- Application Number
- CN202411868559.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the performance of nickel sulfide electrocatalysts is insufficient and the preparation method is complex, making it difficult to achieve efficient, stable and low-cost HER electrocatalysts.
The thin film electrocatalyst is formed by loading the amorphous nickel sulfide/nickel nanosheets agglomerated into spherical shapes on the surface of the foam nickel, and the preparation process is simplified by the electrodeposition method.
An electrocatalyst with high catalytic activity and good stability for alkaline electrolytic water cathode reaction under high current density is realized, and the preparation method is simple and easy to operate.
Smart Images

Figure CN119710801A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nanomaterial technology and electrochemical energy conversion technology, and specifically relates to an amorphous nickel sulfide / nickel nanosheet electrocatalyst and a preparation method and application thereof. Background Art
[0002] With the rapid consumption of non-renewable energy such as fossil fuels, oil, coal and natural gas, their existing quantity can no longer meet people's current life. In addition, the use of these traditional energy sources has led to increasingly serious environmental pollution problems. Since traditional energy is still in use, the main issues at present include how to provide low-cost, reliable and environmentally friendly primary energy with the lowest possible carbon emissions. In addition, this energy should be sustainable and available in every region.
[0003] In previous studies, currently, the precious metal catalyst Pt is considered to be a commercial electrocatalyst with low overpotential and fast reaction kinetics research, and they have high stability and good catalytic activity. However, the scarce reserves of these precious metal compounds on the earth limit their large-scale application. Therefore, it is of great significance to explore an efficient, stable and low-cost HER electrocatalyst. Compared with precious metal materials, transition metal materials have shown great advantages in reserves, price and environmental friendliness. Therefore, transition metal compound catalytic materials are expected to replace precious metal materials as highly active catalysts.
[0004] In the past few years, transition metal compounds have been mainly used as bifunctional electrocatalysts for water electrolysis. They are collectively referred to as TMXs, where TM represents transition metals, X represents non-metallic elements, and s is the aggregate of these substances. For these transition metal catalysts, the components that can really play a role in the catalytic process are different depending on the reaction. Among them, nickel sulfide has become a promising candidate for efficient HER electrocatalysts due to its low cost, high abundance and excellent catalytic performance. However, the HER electrocatalytic performance of the most reported nickel sulfide is still not comparable to that of the benchmark Pt. There are various synthesis methods for nickel sulfide in the prior art, including hydrothermal method, precipitation method and chemical vapor deposition, which can regulate its morphology and crystal structure to optimize the electrocatalytic performance and other complex methods. However, these preparation methods usually involve complex precursors or harsh reaction conditions.
[0005] Therefore, it is very important to develop a simple and easy method to prepare nickel sulfide electrocatalysts with high electrochemical activity and stability. Summary of the invention
[0006] The purpose of the present invention is to provide an amorphous nickel sulfide / nickel nanosheet electrocatalyst and a preparation method and application in order to solve at least one of the above problems, so as to solve the problems of insufficient performance of nickel sulfide electrocatalysts in the prior art and complicated preparation methods. The prepared spherical amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam has high catalytic activity and good stability for the cathode reaction of alkaline water electrolysis at high current density, and the preparation method is simple and easy to operate.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide an amorphous nickel sulfide / nickel nanosheet electrocatalyst, wherein the base material of the electrocatalyst is nickel foam, and amorphous nickel sulfide / nickel nanosheets agglomerated into spherical shapes are loaded on the surface of the nickel foam to form a thin film electrocatalyst.
[0009] The second technical solution of the present invention is to provide a method for preparing the above-mentioned amorphous nickel sulfide / nickel nanosheet electrocatalyst, comprising the following steps:
[0010] (1) ultrasonic cleaning of nickel foam;
[0011] (2) placing the nickel foam cleaned in step (1) in a nickel plating solution containing thiourea for electrodeposition to generate amorphous nickel sulfide / nickel nanosheets aggregated into spherical shapes and loaded on the surface of the nickel foam, thereby forming a thin film electrocatalyst on the surface of the nickel foam.
[0012] The principle of loading amorphous nickel sulfide / nickel nanosheets in the form of spherical agglomerates on the surface of nickel foam to form a thin film is that the nickel foam undergoes an electrodeposition reaction in a nickel plating solution, so that sulfur and nickel are co-deposited on the surface of the nickel foam, and an amorphous nickel sulfide / nickel nanosheet thin film is generated at room temperature. Compared with other methods for preparing effective HER catalysts, the method provided by the present invention is very simple and effective, and does not involve any complex precursors or hydrothermal reactions.
[0013] Furthermore, in step (1), the nickel foam is ultrasonically cleaned with H2SO4 solution, anhydrous ethanol solution and distilled water in sequence.
[0014] Furthermore, in step (2), the current density of the electrodeposition is 4 to 6 A·dm -2 , preferably 5A·dm -2 .
[0015] Furthermore, in step (2), the main salt in the nickel plating solution is nickel sulfate.
[0016] Furthermore, in step (2), the concentration of thiourea in the nickel plating solution is 0.8 to 8 g / L.
[0017] Furthermore, in step (2), the electrodeposition time is 8 to 10 minutes.
[0018] The concentration of thiourea and the electrodeposition time affect the generation of amorphous nickel sulfide / nickel nanosheet electrocatalysts and the content of Ni and S. Within the above range, amorphous nickel sulfide / nickel nanosheets can be generated relatively quickly and have high electrocatalytic activity and good stability.
[0019] Furthermore, in step (2), the concentration of thiourea in the nickel plating solution is 3.2 g / L, and the electrodeposition time is 10 min. Under these conditions, the amorphous nickel sulfide / nickel nanosheet electrocatalyst loaded on the surface of nickel foam prepared by electrodeposition has the best electrocatalytic activity and stability.
[0020] Furthermore, the mass percentage of S in the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst supported on the surface of nickel foam is 5-8%.
[0021] Furthermore, the mass percentage of S in the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst supported on the surface of nickel foam is 6.4%.
[0022] The third technical solution of the present invention is to provide an application of the above-mentioned amorphous nickel sulfide / nickel nanosheet electrocatalyst in the electrolysis of water for hydrogen evolution reaction.
[0023] Furthermore, a three-electrode system is used in the electrolysis of water for hydrogen evolution reaction, wherein the working electrode is the amorphous nickel sulfide / nickel nanosheet, the counter electrode is a graphite electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is a 1.0M KOH solution.
[0024] Furthermore, the amorphous nickel sulfide / nickel nanosheet is used as a cathode material to electrolyze water under alkaline conditions, and the cathode has a current density of 10 mA cm -2 The overpotential is only 61 mV, which has both efficient electrocatalytic activity and good stability. -2 The HER performance remains stable for 30 hours at the current density.
[0025] The self-supporting catalyst obtained by the electrodeposition method has low cost, good controllability, simple operation, and can expose more active sites. The present invention uses the electrodeposition method to generate an amorphous nickel sulfide / nickel nanosheet film and loads it on the surface of nickel foam, so that the HER performance can be kept stable for a long time. The electrocatalyst has good stability under alkaline conditions, and the amorphous nickel sulfide / nickel nanosheet film has high catalytic activity as an electrocatalyst.
[0026] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] 1. The amorphous nickel sulfide / nickel nanosheets prepared by the present invention are prepared by an electrodeposition reaction, so that sulfur and nickel are co-deposited on the surface of nickel foam, thereby obtaining an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam. There is no binder between the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst and the nickel foam, and such a self-supporting structure ensures good conductivity and effective charge transfer between the electrocatalyst and the nickel foam.
[0029] 2. The amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst prepared by the present invention exhibits good long-term stability in alkaline electrolyte. When used as cathode material, water electrolysis and hydrogen evolution are carried out under alkaline conditions. The cathode has a good stability at a current density of 10 mA cm -2 The overpotential is only 61 mV, which has both efficient electrocatalytic activity and good stability. -2 The HER performance remains stable for 30 hours at the current density.
[0030] 3. The preparation method of the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam of the present invention is a one-step electrodeposition method. The preparation method has mild conditions, short reaction time and is easy to operate. The amorphous nickel sulfide / nickel nanosheet thin film loaded on the surface of nickel foam shows excellent catalytic performance and stability for the electrolysis of water HER reaction. Compared with other methods for preparing effective HER catalysts, the method provided by the present invention is very simple and effective, and does not involve any complex precursors or hydrothermal reactions.
[0031] 4. The method of the present invention is simple, easy to operate, and easy to expand to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a diagram of the process of preparing an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam according to Example 1 of the present invention.
[0033] Figure 2 The schematic diagram of the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam prepared in Example 1 of the present invention and the schematic diagram of water electrolysis.
[0034] Figure 3 This is a SEM image of the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst supported on the surface of nickel foam prepared in Example 1 of the present invention.
[0035] Figure 4 TEM image of the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam prepared in Example 1 of the present invention;
[0036] Figure 5 This is an X-ray diffraction pattern of the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam prepared in Example 1 of the present invention.
[0037] Figure 6 This is a polarization curve diagram of the HER of the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam prepared in Example 1 of the present invention in 1.0M KOH solution for water electrolysis.
[0038] Figure 7 This is a graph showing the voltage variation over time under constant current conditions in an experiment of electrolyzing water to release hydrogen in a 1.0 M KOH solution using an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0040] Unless otherwise specified, the experimental reagents and raw materials used in the present invention are commercially available.
[0041] The experimental methods without specific conditions in the following implementations are all selected according to conventional methods and conditions, or according to the product instructions. Unless otherwise specified, the experimental instruments used in the present invention are all conventional experimental instruments in the laboratory.
[0042] Example 1
[0043] 1. Preparation of thiourea-containing nickel electroplating solution
[0044] Weigh 17.5 g of nickel sulfate hexahydrate and 5 g of boric acid and dissolve them in 100 mL of distilled water, and stir at room temperature until they are completely dissolved to prepare a nickel plating solution;
[0045] Weigh 0.4 g of thiourea, dissolve it in the above nickel plating solution, stir at room temperature until it is completely dissolved, and adjust the volume to 125 mL. The thiourea concentration in the prepared thiourea-containing nickel plating solution is 3.2 g / L.
[0046] 2. Preparation of nickel foam
[0047] The 0.5 mm thick nickel foam was cut into 10 × 10 mm size, immersed in 0.5 mol / L sulfuric acid solution and anhydrous ethanol solution for 10 min, and finally ultrasonically cleaned with distilled water for three times;
[0048] 3. Preparation of 1.0M KOH solution
[0049] Take 5.61 g of potassium hydroxide and stir to dissolve in 50 mL of ultrapure water. After cooling, make up to 100 mL.
[0050] 4. Preparation of amorphous nickel sulfide / nickel nanosheet films loaded on nickel foam surface
[0051] (1) Figure 1-Figure 2 As shown, the pretreated nickel foam was fixed with a platinum electrode clamp as the cathode, and the graphite electrode was used as the anode. The nickel sulfide / nickel mixture was electroplated in the nickel plating solution. The power supply current was set to 0.1A and the electrodeposition area was 2cm -2 , the electrodeposition time is 10min.
[0052] (2) After the electroplating is completed, dry it naturally at room temperature;
[0053] (3) The product obtained in step (2) is repeatedly rinsed with distilled water and dried at room temperature to obtain an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of nickel foam.
[0054] The SEM image of the amorphous nickel sulfide / nickel nanosheet film loaded on the surface of nickel foam prepared in Example 1 is as follows: Figure 3 As shown in the TEM image Figure 4 The X-ray diffraction pattern is shown in Figure 5 shown.
[0055] like Figure 3 As shown, the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of nickel foam prepared in this embodiment has a stacked spherical agglomerate structure, indicating that the deposition of amorphous nickel sulfide / nickel nanosheets on the surface of nickel foam increases the active sites on the surface of nickel foam.
[0056] like Figure 4 As shown, the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of the nickel foam prepared in this example has a nanosheet structure, indicating that the nickel foam successfully deposits amorphous nickel sulfide / nickel nanosheets in the nickel plating solution.
[0057] like Figure 5 As shown, the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of nickel foam prepared in this embodiment is consistent with the (111), (200) and (220) crystal planes of pure nickel phase (JCPDS No.04-0850), but the peak width is significantly widened, indicating that the film deposited on the surface of nickel foam is amorphous, that is, amorphous nickel sulfide.
[0058] 5. The electrocatalyst prepared in the example is subjected to an electrocatalytic reaction test, and the specific steps are as follows:
[0059] (1) Activation treatment of electrocatalyst:
[0060] A three-electrode system was used, wherein the working electrode was the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam prepared in the example, the counter electrode was a graphite electrode, the reference electrode was a Hg / HgO electrode, and the electrolyte was 1.0 M KOH;
[0061] Cyclic voltammetry (CV) activation: The Netherlands IVIUM electrochemical workstation was used to perform cyclic voltammetry activation. The test interval was -0.8 to 0 V vs. RHE, the scan rate was 50 mV / s, and the cycle was 30 times until the electrode reached a stable state.
[0062] (2) Linear sweep voltammetry (LSV) test:
[0063] After activation, the program was switched to linear sweep voltammetry with a test interval of -0.5 to 0 V vs. RHE and a scan rate of 5 mV / s;
[0064] (3) Stability test:
[0065] After activation, the program was switched to the multi-step current method program, and the current density was set to 10 mA cm -2 , the time is set to 2592000s (=30h).
[0066] The test results are as follows Figure 6-Figure 7 As shown. Figure 6 It can be seen that the amorphous nickel sulfide / nickel nanosheet film loaded on the surface of nickel foam prepared in Example 1 is used as the cathode material, and water is electrolyzed to produce hydrogen under alkaline conditions. The cathode has a current density of 10 mA cm -2 When the overpotential is 61mV, Figure 7 It can be seen that in the stability test, the voltage change of the electrocatalyst prepared in Example 1 is not large, which proves its good stability.
[0067] Example 2
[0068] 1. Preparation of thiourea-containing nickel electroplating solution
[0069] Weigh 17.5 g of nickel sulfate hexahydrate and 5 g of boric acid and dissolve them in 100 mL of distilled water, and stir at room temperature until they are completely dissolved to prepare a nickel plating solution;
[0070] Weigh 0.2 g of thiourea, dissolve it in the above nickel plating solution, stir at room temperature until it is completely dissolved, and adjust the volume to 125 mL. The thiourea concentration in the prepared thiourea-containing nickel plating solution is 1.6 g / L.
[0071] 2. Preparation of nickel foam
[0072] The 0.5 mm thick nickel foam was cut into 10 × 10 mm size, immersed in 0.5 mol / L sulfuric acid solution and anhydrous ethanol solution for 10 min, and finally ultrasonically cleaned with distilled water for three times;
[0073] 3. Preparation of 1.0M KOH solution
[0074] Take 5.61 g of potassium hydroxide and stir to dissolve in 50 mL of ultrapure water. After cooling, dilute to 100 mL.
[0075] 4. Preparation of amorphous nickel sulfide / nickel nanosheet films loaded on nickel foam surface
[0076] (1) The pretreated nickel foam was fixed with a platinum electrode clamp as the cathode, and the graphite electrode was used as the anode. The nickel sulfide / nickel mixture was electroplated in the nickel plating solution. The power supply current was set to 0.1 A and the electrodeposition area was 2 cm -2 , the electrodeposition time is 8min.
[0077] (2) After the electroplating is completed, dry it naturally at room temperature;
[0078] (3) The product obtained in step (2) is repeatedly rinsed with distilled water and dried at room temperature to obtain an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of the nickel foam.
[0079] 5. The electrocatalyst prepared in the example was subjected to an electrocatalytic reaction test, and the test steps were consistent with those in Example 1.
[0080] The results show that the amorphous nickel sulfide / nickel nanosheet film loaded on the surface of nickel foam prepared in Example 2 is used as the cathode material for electrolysis of water under alkaline conditions to produce hydrogen. The cathode has a high current density of 10 mA cm -2 When the overpotential is 90mV.
[0081] Example 3
[0082] 1. Preparation of thiourea-containing nickel electroplating solution
[0083] Weigh 17.5 g of nickel sulfate hexahydrate and 5 g of boric acid and dissolve them in 100 mL of distilled water, and stir at room temperature until they are completely dissolved to prepare a nickel plating solution;
[0084] Weigh 0.6 g of thiourea, dissolve it in the above nickel plating solution, stir at room temperature until it is completely dissolved, and adjust the volume to 125 mL. The thiourea concentration in the prepared thiourea-containing nickel plating solution is 4.8 g / L.
[0085] 2. Preparation of nickel foam
[0086] The 0.5 mm thick nickel foam was cut into 10 × 10 mm size, immersed in 0.5 mol / L sulfuric acid solution and anhydrous ethanol solution for 10 min, and finally ultrasonically cleaned with distilled water for three times;
[0087] 3. Preparation of 1.0M KOH solution
[0088] Take 5.61 g of potassium hydroxide and stir to dissolve in 50 mL of ultrapure water. After cooling, dilute to 100 mL.
[0089] 4. Preparation of amorphous nickel sulfide / nickel nanosheet films loaded on nickel foam surface
[0090] (1) The pretreated nickel foam was fixed with a platinum electrode clamp as the cathode, and the graphite electrode was used as the anode. The nickel sulfide / nickel mixture was electroplated in the nickel plating solution. The power supply current was set to 0.1 A and the electrodeposition area was 2 cm -2 , the electrodeposition time is 8min.
[0091] (2) After the electroplating is completed, dry it naturally at room temperature;
[0092] (3) The product obtained in step (2) is repeatedly rinsed with distilled water and dried at room temperature to obtain an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of the nickel foam.
[0093] 5. The electrocatalyst prepared in the example was subjected to an electrocatalytic reaction test, and the test steps were consistent with those in Example 1.
[0094] The results show that the amorphous nickel sulfide / nickel nanosheet film loaded on the surface of nickel foam prepared in Example 2 is used as the cathode material for electrolysis of water under alkaline conditions to produce hydrogen. The cathode has a high current density of 10 mA cm -2 When , the overpotential is 73mV.
[0095] Example 4
[0096] 1. Preparation of thiourea-containing nickel electroplating solution
[0097] Weigh 17.5 g of nickel sulfate hexahydrate and 5 g of boric acid and dissolve them in 100 mL of distilled water, and stir at room temperature until they are completely dissolved to prepare a nickel plating solution;
[0098] Weigh 1.0 g of thiourea, dissolve it in the above nickel plating solution, stir at room temperature until it is completely dissolved, and adjust the volume to 125 mL. The thiourea concentration in the prepared thiourea-containing nickel plating solution is 6.4 g / L.
[0099] 2. Preparation of nickel foam
[0100] The 0.5 mm thick nickel foam was cut into 10 × 10 mm size, immersed in 0.5 mol / L sulfuric acid solution and anhydrous ethanol solution for 6 min, and finally ultrasonically cleaned with distilled water for three times;
[0101] 3. Preparation of 1.0M KOH solution
[0102] Take 5.61 g of potassium hydroxide and stir to dissolve in 50 mL of ultrapure water. After cooling, make up to 100 mL.
[0103] 4. Preparation of amorphous nickel sulfide / nickel nanosheet films loaded on nickel foam surface
[0104] (1) The pretreated nickel foam was fixed with a platinum electrode clamp as the cathode, and the graphite electrode was used as the anode. The nickel sulfide / nickel mixture was electroplated in the nickel plating solution. The power supply current was set to 0.1 A and the electrodeposition area was 2 cm -2 , the electrodeposition time is 10min.
[0105] (2) After the electroplating is completed, dry it naturally at room temperature;
[0106] (3) The product obtained in step (2) is repeatedly rinsed with distilled water and dried at room temperature to obtain an amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst deposited on the surface of nickel foam.
[0107] 5. The electrocatalyst prepared in the example was subjected to an electrocatalytic reaction test, and the test steps were consistent with those in Example 1.
[0108] The results show that the amorphous nickel sulfide / nickel nanosheet film loaded on the surface of nickel foam prepared in Example 2 is used as the cathode material for electrolysis of water under alkaline conditions to produce hydrogen. The cathode has a high current density of 10 mA cm -2 When the overpotential is 120mV.
[0109] The preparation parameters of Examples 1-4 are shown in Table 1:
[0110] Table 1 Preparation parameters and measurement results of amorphous nickel sulfide / nickel nanosheet thin film electrocatalysts of Examples 1-4
[0111]
[0112] As shown in Table 1, when the concentration of thiourea in the nickel plating solution is 3.2 g / L and the electrodeposition time is 10 min, the amorphous nickel sulfide / nickel nanosheet electrocatalyst loaded on the surface of nickel foam prepared in Example 1 has the best electrocatalytic activity and stability. When it is used as a cathode material to electrolyze water under alkaline conditions, the cathode has a current density of 10 mA cm -2The overpotential is only 61 mV, which has both efficient electrocatalytic activity and good stability. -2 The HER performance remains stable for 30 hours at the current density.
[0113] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An amorphous nickel sulfide / nickel nanosheet electrocatalyst, characterized in that: The substrate material of the electrocatalyst is nickel foam, and amorphous nickel sulfide / nickel nanosheets agglomerated into spheres are loaded on the surface of the nickel foam to form a thin film electrocatalyst.
2. A method for preparing the amorphous nickel sulfide / nickel nanosheet electrocatalyst as claimed in claim 1, characterized in that: The steps include: (1) ultrasonic cleaning of nickel foam; (2) placing the nickel foam cleaned in step (1) in a nickel plating solution containing thiourea for electrodeposition to generate amorphous nickel sulfide / nickel nanosheets aggregated into spherical shapes and loaded on the surface of the nickel foam, thereby forming a thin film electrocatalyst on the surface of the nickel foam.
3. The method for preparing an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 2, characterized in that: In step (1), the nickel foam is ultrasonically cleaned with H2SO4 solution, anhydrous ethanol solution and distilled water in sequence.
4. The method for preparing an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 2, characterized in that: In step (2), the current density of the electrodeposition is 4 to 6 A·dm -2 .
5. The method for preparing an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 2, characterized in that: In step (2), the main salt in the nickel plating solution is nickel sulfate.
6. The method for preparing an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 2, characterized in that: In step (2), the concentration of thiourea in the nickel plating solution is 0.8-8 g / L.
7. The method for preparing an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 2, characterized in that: In step (2), the electrodeposition time is 8 to 10 minutes.
8. The method for preparing an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 1, characterized in that: The mass percentage of S in the amorphous nickel sulfide / nickel nanosheet thin film electrocatalyst loaded on the surface of nickel foam is 5-8%.
9. Use of the amorphous nickel sulfide / nickel nanosheet electrocatalyst as claimed in claim 1 in hydrogen evolution reaction by electrolysis of water.
10. The use of an amorphous nickel sulfide / nickel nanosheet electrocatalyst according to claim 9, characterized in that: The three-electrode system is used in the electrolytic water hydrogen evolution reaction, the working electrode is the amorphous nickel sulfide / nickel nanosheet, the counter electrode is a graphite electrode, the reference electrode is a Hg / HgO electrode, and the electrolyte is a 1.0M KOH solution.